Mengimplementasikan Rasio Keuangan Untuk Mengukur Nilai Perusahaan Pada Perusahaan Food and Beverage yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019 - Sinta Sinta; Gendro Wiyono (JURNAL ILMIAH EDUNOMIKA, 2021)
The purpose of this research is to determine the influence of profitability, liquidity and leverage on the value of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2019. The population used in this study was a food and beverage sub-sector manufacturing company listed on the Indonesia Stock Exchange for the period 2015-2019 which amounted to 28 companies. Based on sampling techniques used purposive sampling obtained samples as many as 12 companies. The analysis method used is multiple linear regression analysis with SPSS application tools. The results of this study show that: (1) Profitability has a significant positive effect on the Company's Value. (2) Liquidity has no effect on the Company's Value. (3) Leverage has no effect on the Company's Value. (4) Profitability, Liquidity and Leverage simultaneously have a positive and significant effect on the Company's Value. Keywords: Financial Ratio, Profitability, Liquidity, Leverage, Company Value.